Pengembangan Bahan Ajar Menulis Puisi Melalui Media Pembelajaran Buku Tiga Dimensi pada Siswa Kelas X SMK Swasta Abdi Negara Binjai - Winastasia, Novia; Rita, Rita; Lubis, Hasrita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to assess the validity, practicality, and effectiveness of three-dimensional book learning media for writing poetry in class X. Employing the 4D Research and Development model (Define, Design, Development, Disseminate), the quantitative approach and Pre-Experimental Design were utilized for data analysis and media effectiveness testing, respectively. Validation involved four participants: two material experts (90.66%) and two media experts (89%), all categorized as "Very Good." Practicality assessments by 32 subject teachers and X ODTKP students yielded "Very Good" ratings (94% and 87.02%, respectively). Media effectiveness was confirmed by a posttest average (75) surpassing the pretest average (57.62). Inferential statistical analysis (t test) revealed a significant difference (tCount = 14.00, tTable = 1.69), supporting the conclusion that the three-dimensional book media effectively enhances poetry writing learning for class X at SMK Abdi Negara Binjai.